1986
DOI: 10.1093/rheumatology/25.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre Study of Piroxicam Versus Naproxen in Juvenile Chronic Arthritis, With Special Reference to Problem Areas in Clinical Trials of Nonsteroidal Anti-Inflammatory Drugs in Childhood

Abstract: Clinical trials of nonsteroidal anti-inflammatory drugs (NSAIDs) are necessary in juvenile chronic arthritis (JCA) but pose certain problems highlighted and discussed in this study, including recruitment, the assessment of efficacy, and the heterogeneity of the disease. In a multicentre 8-week double-blind cross-over study using the double-dummy technique, piroxicam was compared with naproxen in 47 children with seronegative JCA aged 5-16 years. No significant difference between the two treatments was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…This indicates that the toxicity index may be clinically important in the assessment of drug toxicity in children over time, but the implications of our results are hard to assess because of the difficulty of statistical comparison. Exposure to ibuprofen, naproxen, antimalarials and methotrexate has previously resulted in 5-24% side-effects in controlled randomised trials of children treated with these drugs [7,9,[24][25][26], but in contrast to the tendency in our study, an equal tolerance of piroxicam and naproxen has been found in short-term randomised trials [8,27].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This indicates that the toxicity index may be clinically important in the assessment of drug toxicity in children over time, but the implications of our results are hard to assess because of the difficulty of statistical comparison. Exposure to ibuprofen, naproxen, antimalarials and methotrexate has previously resulted in 5-24% side-effects in controlled randomised trials of children treated with these drugs [7,9,[24][25][26], but in contrast to the tendency in our study, an equal tolerance of piroxicam and naproxen has been found in short-term randomised trials [8,27].…”
Section: Discussioncontrasting
confidence: 97%
“…Data on drug toxicity during long-lasting juvenile rheumatic diseases are scarce. Thus toxicity during 2 or more years of treatment has previously been reported in retrospective studies for some antirheumatic drugs [4][5][6], and drug tolerance has been assessed in prospective randomised trials, but these latter studies have, to our knowledge, only lasted for 2-12 months [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…GI AE have been observed in a number of clinical trials in children with JRA using NSAID 4,[9][10][11][15][16][17][18][19][20][21][22][23] . A number of clinical trials and observational studies have also been conducted to determine the prevalence of GI complications of NSAID therapies over time, in a real-world clinical setting.…”
Section: Rheumatologymentioning
confidence: 99%
“…Piroxicam, an oxicam derivative, which is known for its long t'l2 (""36h) has been found effective in juvenile arthritis patients (Garcia- Morteo et al 1987;Tyndall & Ansell 1980;Williams et al 1986). Dosage recommendations are not available, but an average dose of piroxicam 0.33 mg/kg/day given once daily was used in most of the above trials.…”
Section: Other Nsaidsmentioning
confidence: 99%